Kajian Prosedur Pencatatan Hak Cipta Karya Fotografi - Wahyu Suwarni (Politeknik Negeri Media Kreatif, 2017)
The declarative principle contained in the Copyright Act, makes people reluctant to record the copyright of photographic works. In the absence of the creation letter, neither the creator nor the copyright holder has obtained any legal certainty. The purpose of this research is to provide the use of copyright logging procedures especially in photographic works. The method used in this study is normative juridical. The procedure for copyright application in order consists of: Register an account on the official website of DJKI; Uploading files about the statement letter, transfer of rights, and examples of creation; Making payments; Approve application for creation; Certificate (Letter of Creation). Based on this study, the recording of creation means creating material rights.